IZAR - User Guide - Ivanytska, Vitaliya (2012)
The goal of this paper is to explore a newly designed software support for solving multi-criteria decision-making problems -- IZAR, as well as to create a comprehensible manual for a common user interested in decision-making theory. IZAR is currently in a development stage; nevertheless, its available versions are already being used by operations research students. The first two sections of this thesis are focused on a brief introduction of all the solutions methods used in the current version of IZAR, while the third section is a practical user guide that includes examples of the problems and a comparative summary of different ways of their solution reached by the means of IZAR.